2017
DOI: 10.3390/s17061224
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Study between RMS and Edge Detection Image Processing Algorithms for a Pulsed Laser UWPI (Ultrasonic Wave Propagation Imaging)-Based NDT Technique

Abstract: In this study, a non-contact laser ultrasonic propagation imaging technique was applied to detect the damage of plate-like structures. Lamb waves were generated by an Nd:YAG pulse laser system, while a galvanometer-based laser scanner was used to scan the preliminarily designated area. The signals of the structural responses were measured using a piezoelectric sensor attached on the front or back side of the plates. The obtained responses were analyzed by calculating the root mean square (RMS) values to achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…The vibration energy distribution is the basis for a simple but very efficient technique that utilizes the calculation of a root mean square (RMS). Recently, the RMS has been successfully used to detect defects in aluminium plates [14][15][16], delamination in a composite T-joint [17], disbonds in a stiffened panel [18], notches and corrosion areas in aluminium plates [19], disbond inserts in composite elements [20] and voids in adhesive joints [7]. The root mean square for a continuous signal s(t) is calculated with respect to the formula:…”
Section: Root Mean Squarementioning
confidence: 99%
“…The vibration energy distribution is the basis for a simple but very efficient technique that utilizes the calculation of a root mean square (RMS). Recently, the RMS has been successfully used to detect defects in aluminium plates [14][15][16], delamination in a composite T-joint [17], disbonds in a stiffened panel [18], notches and corrosion areas in aluminium plates [19], disbond inserts in composite elements [20] and voids in adhesive joints [7]. The root mean square for a continuous signal s(t) is calculated with respect to the formula:…”
Section: Root Mean Squarementioning
confidence: 99%
“…This processing technique depends on the calculation of the weighted root mean square for each registered time signal and the creation of a damage map. The WRMS for a time signal s(t) can be defined as follows [25,26,30,33,36]…”
Section: Weighted Root Mean Square Damage Imagingmentioning
confidence: 99%
“…This method was improved to be more applicable for damage detection by defining the weighted root mean square (WRMS) method [30]. Recently, the RMS has been successfully used in various damage detection applications [25,26,[31][32][33][34][35][36].Żak et al [30] investigated aluminum and composite plates as well as composite elements of a helicopter, all with the damage being simulated by an additional mass. They concluded that better resolution in WRMS maps corresponded to higher values of the weighting factor (linear or square).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the rapid development of laser machining technology, laser machining systems with galvano scanners have become indispensable in laser processing industrial techniques such as welding, cutting, sculpting, drilling, marking, mode filling, and surface treatment. (1)(2)(3)(4)(5)(6) The laser machining systems with galvano scanners can be used to effectively replace the traditional machinery machining approach according to the following advantages: (1) noncontact treatment, (2) absence of pollution, (3) high movement speed, (4) prevention of tool wear, (5) high precision, and (6) high efficiency. In addition, the laser galvanometer scanning systems are widely utilized in material processing because they can control the laser spot more accurately and rapidly than other scanning systems for producing a small and uniform laser spot size in an objective flat field.…”
Section: Introductionmentioning
confidence: 99%